Visual Semiotics and Symbolic Language in the Film Omar - Jawahir, Ach (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
One of the famous religious films widely watched by Muslims is Omar. In this film, there are many visual semiotics and symbolic languages ​​that can be studied to reveal the denotative, connotative, and ideological meanings built through cinematic elements. However, this study only focuses on the "Omar" film series in episodes one, two and three. The purpose of the study is to uncover and understand the symbols contained in the "Omar" film series one, two and three, the data is analyzed qualitatively using Roland Barthes' semiotic framework through observation, documentation, and recording of visual and verbal signs, research data is taken from several things, such as film scene cuts, dialogue, costume selection, lighting and visual composition that reflect religious and historical symbols. The data collection technique is carried out through in-depth observation (close viewing), documentation, and recording of relevant visual and verbal codes. Data analysis in this study is carried out in several stages, the first stage, namely the identification of signs (signifier-signified). The second stage is interpreting the meaning of denotation and connotation. The third stage is the interpretation of the myths and ideologies contained in the visual narrative of the film "Omar." The expected results of this research will be able to explain and provide a deeper understanding to religious film enthusiasts, literature enthusiasts, and historians, especially Muslims worldwide, about how the film "Omar" constructs Islamic values, depicts religious beliefs through symbolism, and provides academic contributions to the study of film semiotics and religious visual communication.